The Evolution of Georgia-Russia Relations (2003-2008): a SWOT Analysis of Geopolitical Tensions, Economic Pressures and Strategic Opportunities - Ghazaryan, Karen («ԱՐՑԱԽ» հրատ.)
This article examines the evolution of relations between Georgia and the Russian Federation, particularly in the period leading up to the "Five-Day" War, which significantly changed the dynamics of relations between the two nations. Focusing on the period following Georgia's Rose Revolution in 2003, the study analyzes the changing nature of bilateral relations, the influencing factors and challenges faced by both sides amid changing geopolitical developments. The purpose of the study is to understand how Georgia navigated the complex geopolitical landscape, balancing its aspirations for NATO and EU membership with its ongoing territorial disputes with Russia. The central research question is: How did Georgia’s foreign policy during 2003-2008 address its geopolitical vulnerabilities and opportunities in the face of Russian opposition? The study applies a SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats) methodology to evaluate Georgia’s foreign policy decisions in this critical period, considering both internal and external factors. The findings highlight the strategic importance of Georgia’s geographic location and political reforms but also reveal significant vulnerabilities, including unresolved territorial conflicts and dependence on Western support without formal security guarantees. Այս հոդվածում ուսումնասիրվում է Վրաստանի և Ռուսաստանի Դաշնության միջև հարաբերությունների զարգացումը, հատկապես «Հինգօրյա» պատերազմին նախորդող շրջանում, որը էականորեն փոխեց երկու երկրների միջև հարաբերությունների դինամիկան։ Հոդվածում հատուկ ուշադրության են արժանանում 2003 թվականի «Վարդերի» հեղափոխությունից հետո Վրաստանի արտաքին քաղաքականության փոփոխվող բնույթը, երկկողմ հարաբերությունների վրա ազդեցություն ունեցող գործոնները և կողմերի դիմագրաված մարտահրավերները՝ փոխվող աշխարհաքաղաքականության զարգացումների ֆոնին։ Ուսումնասիրության նպատակն է հասկանալ, թե ինչպես Վրաստանը հաղթահարեց աշխարհաքաղաքական մարտահարավերները՝ հավասարակշռելով ՆԱՏՕ-ին և ԵՄ-ին անդամակցելու իր հավակնությունները՝ Ռուսաստանի հետ շարունակվող տարածքային վեճերի ֆոնին։ Հետազոտության հիմնական հարցն է՝ ինչպես է Վրաստանի արտաքին քաղաքականությունը 2003-2008 թվականներին արձագանքել իր աշխարհաքաղաքական խոցելիություններին ու հնարավորություններին՝ Ռուսաստանի հակադրությամբ։ В данной статье рассматривается эволюция отношений между Грузией и Российской Федерацией, особенно в период, предшествующий «Пятидневной войне», которая существенно изменила динамику отношений между двумя странами. Сосредотачиваясь на периоде после «Революции роз» в Грузии в 2003 году, исследование анализирует изменяющийся характер двусторонних отношений, факторы влияния и вызовы, с которыми сталкивались обе стороны на фоне меняющихся геополитических событий. Цель исследования - понять, как Грузия ориентировалась в сложной геополитической обстановке, балансируя между стремлением к вступлению в НАТО и ЕС и продолжающимися территориальными спорами с Россией. Ключевой вопрос исследования: как внешняя политика Грузии в 2003-2008 годах учитывала её геополитические уязвимости и возможности на фоне противостояния с Россией? В исследовании применяется методология SWOT-анализа (сильные стороны, слабые стороны, возможности и угрозы) для оценки внешнеполитических решений Грузии в этот критический период с учетом как внутренних, так и внешних факторов. Результаты исследования отмечают стратегическое значение географического положения Грузии и политических реформ, но также выявляют значительные уязвимости, включая нерешенные территориальные конфликты и зависимость от западной поддержки без формальных гарантий безопасности.
Keywords: Political science; International relationships